Analysis of 10 Watt and 15 Watt Universal Wireless Charger - Imammuddin, Azam Muzakhim; Farizal, Mochamad; Hariyadi, Aad (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Conventional battery charging systems for mobile phones predominantly rely on wired power transfer using cables; however, the development of wireless power transfer (WPT) technology has enabled more practical and universal charging solutions. Since its initial introduction in 2009, wireless charging based on inductive coupling has evolved and is now widely implemented in universal wireless chargers with varying power ratings. This research aims to analyze and compare the electrical and operational characteristics of universal wireless charging primary-side devices rated at 10 W and 15 W available on the market. The study focuses on operating frequency, peak-to-peak voltage, effective charging distance, coil parameters, and charging time performance using the same receiver. Experimental measurements were conducted to evaluate frequency response, voltage characteristics, inductive distance capability, and battery charging duration from 0% to 100%. The results show that the 10 W primary device operates at a frequency range of 111–128 kHz with peak-to-peak voltages of 19–26 V and a maximum charging distance of 12 mm, achieving an average charging time of 56.39 minutes per 10% battery increment. In contrast, the 15 W device operates at 118–160 kHz with voltages of 16–24 V, supports a 14 mm charging distance, and requires an average of 68.50 minutes per 10% increment. Both devices exhibit increased voltage and reduced operating frequency under load conditions.